Engineering properties and structural perfomance of rubberized concrete paving blocks - 339614 Ling, Tung Chai; Hasanan Md. Nor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Doktor Falsafah (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2008